Prevalence of dementia in a level 4 university epilepsy center: how big is the problem? - Helmstaedter, Christoph; Lutz, Teresa; Wolf, Vinzent; Witt, Juri-Alexander (Frontiers in Neurology, 2023)
The relationship between epilepsy and dementia is currently a topic of great interest. Our study aimed to determine the prevalence of dementia diagnoses among patients of a large level 4 university epilepsy center.In this retrospective monocentric study conducted at the Department of Epileptology of the University Hospital Bonn, we searched for dementia-related terms in a total of 145,501 medical letters from 40,360 adult patients who were seen between 2003 and 2021. Files with at least one hit were selected and analyzed with regard to diagnoses, age, age at epilepsy onset, and the question as to whether the epilepsy preceded or followed the dementia diagnosis.Results: Among the medical letters of 513 patients, dementia-related terms were found. The letters of 12.7% of these patients stated a dementia diagnosis, 6.6% were suspected of having dementia, 4.9% had mild cognitive impairment, and 6.6% had other neurodegenerative diseases without dementia. Taking all 40,360 patients into account, the prevalence of diagnosed or suspected dementia was 0.25%. An older age (≥60 years) and a late-onset epilepsy (≥60 years), but not a longer epilepsy duration, increased the odds of dementia by 6.1 (CI 3.5-10.7) and 2.9 (CI 1.7-4.7), respectively. Additionally, vascular, metabolic, inflammatory, and behavioral mood-related comorbidities were commonly observed. Epilepsy tended to precede (23.2%) rather than follow (8.1%) the dementia diagnosis.Conclusions: Despite the clear limitations of a selection bias and the potential underdiagnosis of dementia and underestimation of its prevalence when relying on the medical letters from a specialized center which rather focuses on epilepsy-related issues, the findings of this study offer valuable insights from the perspective of an epilepsy center. In this setting the prevalence of dementia in epilepsy is rather low. However, physicians should be aware that the risk of dementia is higher in the elderly, in late-onset epilepsies, and when comorbid risk factors exist. Seizures can also be an early sign of a neurodegenerative disease. Future research should explicitly screen for dementia in patients with epilepsy and stratify them according to their underlying pathologies and comorbidities.